Hak Kebebasan Berpendapat di Media Sosial dalam Perspektif Hak Asasi Manusia (HAM) - Wijaya, Muchsin; Laia, Aturkian (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Freedom of expression is a fundamental human right essential for sustaining democracy. While social media has become the primary space for digital expression, it raises critical concerns regarding the limits of state intervention in maintaining public order without violating human rights. This study aims to analyze the legal standing of freedom of expression on social media from a human rights perspective, its legal boundaries under Indonesian law, and the challenges in its enforcement. Utilizing a normative legal research method with statutory, conceptual, and case approaches, the study reveals that while digital expression is constitutionally protected and guaranteed under Article 19 of the ICCPR, it remains a derogable right open to lawful restriction via the three-part test. However, current provisions in Articles 27A and 28 of the UU ITE produce ambiguities that risk criminalizing legitimate criticism and undermining legal certainty. Consequently, this article recommends refining the UU ITE norms, consistently applying the proportionality test by judges to protect public criticism, and strengthening public legal literacy.